Resolution of difficulties approach for a Community of Practice members: design, implementation and experiment - Belmeskine, Rachid; Begdouri, Ahlame; Groux-Leclet, Dominique (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
MAETIC is a pedagogical method intended to implement the pedagogy of a group per project. When a teacher deploys this method in his classroom, he may encounter difficulties due to the lack of experience and may need help. To support the community of practice of teachers that use the MAETIC method, we design a Community Computing Environment (CCE). This CCE consists of a kernel, a RD (Resolving Difficulties) layer and two adaptations layers. In this paper we detail the kernel that incorporates the basic features of a community environment and the RD layer that permits to assist teachers in solving their problems. This layer is based on Case-Based Reasoning (CBR).